Tick-Borne Encephalitis Virus Infection Alters the Sialome of Ixodes ricinus Ticks During the Earliest Stages of Feeding - Hart, Charles E.; Ribeiro, Jose M.; Kazimirova, Maria; Thangamani, Saravanan (Frontiers in Cellular and Infection Microbiology, 2020)
Ticks are hematophagous arthropods that transmit a number of pathogens while feeding. Among these is tick-borne encephalitis virus (TBEV), a flavivirus transmitted by Ixodes ricinus ticks in the temperate zone of Europe. The infection results in febrile illness progressing to encephalitis and meningitis with a possibility of fatality or long-term neurological sequelae. The composition of tick saliva plays an essential role in the initial virus transmission during tick feeding. Ticks secrete a diverse range of salivary proteins to modulate the host response, such as lipocalins to control the itch and inflammatory response, and both proteases and protease inhibitors to prevent blood coagulation. Here, the effect of viral infection of adult females of Ixodes ricinus was studied with the goal of determining how the virus alters the tick sialome to modulate host tissue response at the site of infection. Uninfected ticks or those infected with TBEV were fed on mice and removed and dissected one- and 3-h post-attachment. RNA from the salivary glands of these ticks, as well as from unfed ticks, was extracted and subjected to next-generation sequencing to determine the expression of key secreted proteins at each timepoint. Genes showing statistically significant up- or down-regulation between infected and control ticks were selected and compared to published literature to ascertain their function. From this, the effect of tick viral infection on the modulation of the tick-host interface was determined. Infected ticks were found to differentially express a number of uncategorized genes, proteases, Kunitz-type serine protease inhibitors, cytotoxins, and lipocalins at different timepoints. These virus-induced changes to the tick sialome may play a significant role in facilitating virus transmission during the early stages of tick feeding.